The Effect of Contextual Teaching and Learning Model for Primary Studentsâ Achievement in Science Class - Paura, Anggi; Lazim, Lazim; Syahrilfuddin, Syahrilfuddin; Hermita, Neni (Proceedings of the UR International Conference on Educational Sciences, 2018)
The Contextual Teaching Learning Model (CTL) makes the learning process that emphasizes the process of student involvement in real life everyday. This study aims to determine the differences in studentsâ science learning outcomes using the CTL model. This research method uses Quasi-Nonequivalent Experiment of Pretest-Postest Design Group. This study was conducted on 56 students who each class amounted to 28 students. Based on the results of the study obtained the results of science learning students learn with the CTL model higher increase than those who study with conventional models. It can be seen from the gain index value in the CTL class of 56% which is the medium category, while the gain index value in the conventional class is 32% which is a low category. This shows that the CTL model can improve the learning outcomes of elementary school students in water saving and natural events.